2017
DOI: 10.1007/s12034-017-1381-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the tension load of rubber composites by impact dynamic testing

Abstract: This work deals with establishing the tension load by impact dynamic testing of rubber composite conveyor belts. The value of tension load affects the shape of the used impactor and use of a support system as well as the weight of the ram and the impact height. An increase in the allowable stress when the belt is tensioned was examined during the test, to determine the effect of impact on the tension load. The obtained values of tension load are assessed using basic mathematical and statistical methods. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The hyperelastic and viscoelastic constitutive model parameters of the rubber material are used as design variables, and a sample space was constructed, as shown in Table 1. The Optimal Latin Hypercube Design is employed to generate test points in the sample space [32]. Then the dynamic stiffness and damping of the corresponding test points are obtained under the cooperative work of ANSYS and MATLAB.…”
Section: Joint Simulation Based On Isightmentioning
confidence: 99%
“…The hyperelastic and viscoelastic constitutive model parameters of the rubber material are used as design variables, and a sample space was constructed, as shown in Table 1. The Optimal Latin Hypercube Design is employed to generate test points in the sample space [32]. Then the dynamic stiffness and damping of the corresponding test points are obtained under the cooperative work of ANSYS and MATLAB.…”
Section: Joint Simulation Based On Isightmentioning
confidence: 99%
“…The dependence of fracture behavior on stress growth rate is" therefore, of great research interest. Experiments on polycrystalline metals have shown that the stress growth rate has significant effects on yield strength [4,5], tensile strength [5,6], fracture toughness [7][8][9], crack tunneling [10], and crack growth speed [11]. Different from polycrystalline metals, nanocrystalline metals have a large grain boundary proportion.…”
Section: Introductionmentioning
confidence: 99%
“…A conveyor belt is a rubber composite material consisting of various materials, such as rubber, fabric, steel, and other materials [1]. It is the most expensive structural component of every belt conveyor, representing 40-60% of the total cost [2].…”
Section: Introductionmentioning
confidence: 99%